The political problem of internal "ἀσφάλεια" in Niketas Choniates' Chronikè Diéghesis: a contributing factor to the Constantinople's fall in 1204 - CATANZARO, Andrea (Byzantina Symmeikta, 2013)
In this essay I analyze the idea of aspháleia (safety) in the political thought of the Byzantine historian Niketas Choniates (1150-55/1217 ca.), as it appears in his Chronikè Diéghesis. This historical work covers the period 1118-1206 and is a very significant source about the history of Byzantine Empire in the XII century and about its fall in the 1204. Particularly I focus on three aspects of the idea of aspháleia in the “second class aristocracy”, as Paul Magdalino defined it in his works. According to Niketa’s thought, the lack of safety in the Empire competes to create in the XII century some preconditions of the Constantinople’s fall in 1204.